Penerapan Model Pembelajaran Kooperatif Tipe Make a Match untuk Meningkatkan Hasil Belajar Siswa pada Materi Larutan Elektrolit dan Non Elekrolit di Kelas X Madrasah Aliya DDI Lonja - Muslimah, Muslimah; Mustapa, Kasmudin; Ratman, Ratman (Jurnal Akademika Kimia, 2018)
This research describes the differences of student’s learning with the application of cooperative learning type make a match in the electrolyte and non-electrolyte at the X grade student’s of the Madrasah Aliya DDI Lonja. This research used quasi experimental with non randomized pretest-posttest control group design. This research was conducted with two groups: XA as the experimental (n=21) XB as the control group (n=18). The data findings means score of experimental group (X1) is 70,5 with the standard deviation 9,6 and the control group (X2) is 62.0 with the standard deviation is 6. Based on the results, the researcher concludes cooperative learning type make a match has better than control class that used conventional learning model.